Topical Application of Bio-Pulsed Avian MSC-Derived Extracellular Vesicles Enhances Hair Regrowth and Skin Rejuvenation: Evidence from Clinical Evaluation and miRNA Profiling - Shieh, Ju-Sheng; Chin, Yu-Tang; Yeh, Tsu-Te; Guo, Jiong Jiong; Chang, Fung-Wei; Cheng, Hui-Rong; Hsu, Hung-Han; Huang, Wei-Lun; Huang, Han-Hsiang; Hsieh, Ya-Yu; Chiang, Chien-Ping; Wang, Shih-Ching (Current Issues in Molecular Biology, 2025)
Small extracellular vesicles (sEVs) derived from mesenchymal stem cells have emerged as promising therapeutic agents in regenerative dermatology. This study evaluated the safety and efficacy of Bio-Pulsed avian mesenchymal stem cell-derived sEVs (AMSC-sEVs), topically applied for hair follicle stimulation and skin rejuvenation. Two prospective, single-arm clinical trials were conducted: one involving 30 participants using a hair ampoule over 60 days, and the other involving 30 participants applying a facial essence for 28 days. Objective measurements demonstrated significant improvements in the anagen/telogen hair ratio, reduced shedding, increased collagen density, and reduced wrinkle depth and pigmentation. Small RNA sequencing and qPCR profiling confirmed that Bio-Pulsed AMSC-sEVs were enriched with regenerative microRNAs, such as miR-21-5p and miR-199a-5p, associated with anti-inflammatory and anti-aging effects. No adverse events were reported. These findings suggest that Bio-Pulsed AMSC-sEVs may offer a safe, non-invasive, and cell-free approach to enhance skin and hair regeneration in human subjects.